Education for Global Citizenship Towards the New European Education Area - Ana Ancheta-Arrabal; Miriam Preckler Galguera (Social Sciences)
Over the last decades, many European educational systems have been reviewing the citizenship education model that they have been developing, trying to deepen the meaning of democratic citizenship practice today or the social demand inspired by the creation of adequate conditions for its exercise. Thus, it is challenging for educational systems to face education for global citizenship, and international organizations have been promoting the development of citizenship education and conducting research in this field. New research and educational practices are expected for global citizenship, and their meaning in our European societies is a point of reference for the study of the different policies that national and supranational institutions promote in this matter. The Council of Europe Charter on Education for Democratic Citizenship and Human Rights Education from 2010 and its counterpart framework from UNESCO in 2015 have actively promoted the idea of citizenship education on a global scale through its Global Citizenship Education Model. The International Association for the Evaluation of Educational Achievement (IEA) conducted a series of reports on social and civic competencies to investigate the extent to which young people are prepared to assume their role as citizens, which recently has been reviewed by Schulz et al. Based on its main findings and the latest survey by the European EACEA/Eurydice from 2023 that covers 15 member countries of the Eurydice Network, this paper presents a cross-national study of the global citizenship education (GCE) between European Countries that updates recent national information and research developments in this field. Based on the analyzed data and the criteria established by UNESCO, the comparative study allows us to determine the dimensions and trends in global citizenship education in order to address its implications within the European education area.